A Critical Review of Phaltrikadi Ghana Vati in the Management of Kamala w.s.r to (Jaundice) - Khuntia, Sandhyarani; Panda, Pradip Kumar; Sahu, Manoranjan; Nayak, Utkalini (International Research Journal of Ayurveda & Yoga, 2022)
In Ayurvedic Classics a number of single drugs and formulations have been mentioned for treatment of liver disorders. Phalatrikadi Ghana vati is one of the important and prestigious formulation, which is successfully used from the ancient period. AIM: The main aim of this review study to know the pharmacological action of this formula on the level of dosha (physiological entity of our body), bhutagni as we know that liver is the main seat of the bhutagni and positive role of Phaltrikadi ghana vati in treatment or avoiding harmful effects of so many agents as drugs, chemicals, toxins and alcohol. Due to the properties like - Pitta, Kapha shamaka, Yakriduttejaka, Shothahara, Pandurogahar, Rechan, Deepan etc. Ghana vati of Triphala (Hareetaki, Vibheetaki and Amalaki), Amrita, Nimba, Tikta (Katuki), Vasa, and Kiratattikta (Bhunimb) taken with honey or warm water pacify the koshthashrit kamala and shakhashrita kamala. Jaundice is a common disorder. The clinical features of jaundice go hand in hand with that of kamala. Phalatrikadi Ghana vati, is being utilized for the management of kamala from ancient time.